HUBUNGAN ANTARA KONSEP DIRI DENGAN KOMUNIKASI INTERPERSONAL PADA MAHASISWA PENDIDIKAN TATA NIAGA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - CORRY YOHANA (Fakultas Ekonomi Universitas Negeri Jakarta, 2014)
Abstract The purpose of this study was to find the relationship between self-concept and interpersonal communication on Commerce Education Students of the Faculty of Economics, State University of Jakarta. This study used a survey method with the correlational approach. While the sampling technique used is simple random techniques (Random Sampling Technique). Affordable population numbered 65 students. The study sample was 55 students selected randomly. The results showed that: that there is a positive relationship between self-concept and interpersonal communication Commerce Education student class of 2009 Faculty of Economics, University of Jakarta. Thus if the self-concept of students increases, the interpersonal communication will also increase. Keywords: self-concept, interpersonal communication.